2023
DOI: 10.1002/jsfa.12460
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, identification, and starch‐digestion inhibition of phenolics from Euryale ferox seed coat

Abstract: BACKGROUND: Euryale ferox is an important cash crop and valuable tonic in traditional medicine. The seeds of E. ferox are rich in starch, which is hard to digest, and the digestion speed is significantly slower than that of rice starch. The goal of this study was to evaluate the effects of E. ferox seed-coat phenolics (EFCPs) on the digestion of E. ferox seed starch. RESULTS: EFCPs were extracted and identified by ultra-high performance liquid chromatography coupled with quadrupole time-of-flight mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…A flavone derivative, 5-hydroxy-2-(4-methoxy-3-((E)-3-methylbut-1-enyl)-5-(3-methylbut-3-enyl)phenyl)chroman-4-one ( Figure 5 a), identified in Andrographis echioides leaf, was found to dramatically inhibit α-amylase (IC 50 = 3.35 µg/mL) and enhance glucose intake in the 3T3-L1 and L6 cell lines [ 134 ]. Another study conducted by Zhang et al [ 136 ] revealed that epicatechin gallate ( Figure 5 b) (IC 50 = 0.92 mg/mL) isolated from Euryale ferox seed coat possessed good inhibitory effects against α-amylase in comparison to acarbose (IC 50 = 1.08 mg/mL). Similarly, Wu and Tian [ 138 ] isolated a new flavone glycoside, tricetin 4′- O -β-glucopyranoside ( Figure 5 c), along with a known flavone, Tricetin ( Figure 5 d), from the flowers of Punica granatum .…”
Section: Secondary Metabolites Isolated From Various Plant Sources As...mentioning
confidence: 99%
“…A flavone derivative, 5-hydroxy-2-(4-methoxy-3-((E)-3-methylbut-1-enyl)-5-(3-methylbut-3-enyl)phenyl)chroman-4-one ( Figure 5 a), identified in Andrographis echioides leaf, was found to dramatically inhibit α-amylase (IC 50 = 3.35 µg/mL) and enhance glucose intake in the 3T3-L1 and L6 cell lines [ 134 ]. Another study conducted by Zhang et al [ 136 ] revealed that epicatechin gallate ( Figure 5 b) (IC 50 = 0.92 mg/mL) isolated from Euryale ferox seed coat possessed good inhibitory effects against α-amylase in comparison to acarbose (IC 50 = 1.08 mg/mL). Similarly, Wu and Tian [ 138 ] isolated a new flavone glycoside, tricetin 4′- O -β-glucopyranoside ( Figure 5 c), along with a known flavone, Tricetin ( Figure 5 d), from the flowers of Punica granatum .…”
Section: Secondary Metabolites Isolated From Various Plant Sources As...mentioning
confidence: 99%